2019
DOI: 10.1109/jsen.2019.2907664
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Epileptic Seizure Detection During Sleep Using Passive Infrared Sensors

Abstract: This paper addresses the problem of detecting epileptic seizures experienced by a human subject during sleep. Commonly used solutions to this problem mostly rely on detecting motion due to seizures using contact-based sensors or video-based sensors. We seek a low-cost, low-power alternative that can sense motion without making direct contact with the subject and provides high detection accuracy. We investigate the use of Passive InfraRed (PIR) sensors to sense human body motion caused by epileptic seizures dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…also created an end‐to‐end model to analyze multiple frames, significantly improving the performance. Nocturnal BTC seizures have been detected in the infrared (IR) spectrum using thermophile sensor arrays and passive IR sensors to detect 1.6–3‐Hz periodic movements 13,51,57,60 . These devices, unlike IR illuminated cameras, produce unidentifiable images, protecting patient privacy while maintaining performance; models achieved up to 93.1% accuracy on patient data and accuracy of 99% on actor‐simulated seizures.…”
Section: Clinical Application In Epilepsymentioning
confidence: 99%
“…also created an end‐to‐end model to analyze multiple frames, significantly improving the performance. Nocturnal BTC seizures have been detected in the infrared (IR) spectrum using thermophile sensor arrays and passive IR sensors to detect 1.6–3‐Hz periodic movements 13,51,57,60 . These devices, unlike IR illuminated cameras, produce unidentifiable images, protecting patient privacy while maintaining performance; models achieved up to 93.1% accuracy on patient data and accuracy of 99% on actor‐simulated seizures.…”
Section: Clinical Application In Epilepsymentioning
confidence: 99%
“…In addition, Hanosh et al. [30] employed PIR sensors to sense human body motion caused by epileptic seizures during sleep. Also, for the detection of obstructive sleep apnoea, a wearable Sleepcare kit was developed in [31].…”
Section: Related Workmentioning
confidence: 99%
“…In [29], on the basis of strip-type force sensors, an unobtrusive sleep monitoring system was developed for awakening and respiration rate analysis during sleep. In addition, Hanosh et al [30] employed PIR sensors to sense human body motion caused by epileptic seizures during sleep. Also, for the detection of obstructive sleep apnoea, a wearable Sleepcare kit was developed in [31].…”
Section: Related Workmentioning
confidence: 99%
“…Studies that are addressing real-time epileptic seizure detection techniques can be found in [145][146][147][148][149]. Hanosh et al [145] used Passive Infrared Sensors (PIR) for realtime epileptic seizure detection during sleep.…”
Section: Epileptic Seizure Detectionmentioning
confidence: 99%
“…Studies that are addressing real-time epileptic seizure detection techniques can be found in [145][146][147][148][149]. Hanosh et al [145] used Passive Infrared Sensors (PIR) for realtime epileptic seizure detection during sleep. In this study, identifying and removing eyeblink artifacts are not applicable as the study focused on seizure detection during sleep, where no eye blinking activity occurs during this stage.…”
Section: Epileptic Seizure Detectionmentioning
confidence: 99%